Пациент-контролирана аналгезија со ремифентанил за безболно породување: ефикасност и ефекти врз мајката и детето - Караџова, Дафина (Медицински факултет, УКИМ, Скопје, 2017)
Introduction: Providing effective and reliable analgesia during labor is a constant challenge for the obstetric anesthesiologist. Epidural analgesia is the most effective method for pain relief in labor and it is considered a gold standard in obstetric anesthesia. However, in moments when epidural analgesia is contraindicated, unwanted by the patient or simply unavailable, remifentanil can be an excellent alternative. Aims: The goals of this research are: to evaluate the efficacy of remifentanil compared to epidural analgesia for a painless birth; to determine the patient's satisfaction; to assess the safety of remifentanil for the mother, fetus and newborn during the entire course of birth; and to determine an effective and safe dose of remifentanil that would be suitable for all parturients. Materials and methods: The prospective, randomized and longitudinal study included 155 pregnant women in term for birth. The patients were randomized into 2 groups: a remifentanil group (RG), and an epidural group (EG). Patients in the RG (80 patients) received intravenous remifentanil administered by a pump for patient-controlled analgesia (PCA) in bolus doses without continuous infusion. Patients in the ЕG (75 patients) received epidural analgesia with programmed intermittent bolus dosing. During labor, the efficacy of anesthesia was evaluated, as well as the satisfaction of the patients through 2 separate VAS scales; the mother's safety was monitored through her complete haemodynamic monitoring (SaO2, respiratory rate, non-invasive blood pressure, heart rate, sedation, nausea, vomiting, itching, fever), for the neonatal safety fetal heart rate (FHR) was monitored with continuous cardiotocograph recording, after delivery the Apgar scores of the 1st, 5th and 10th minute were determined and the acid-base status was measured. Results: The VAS pain scores were significantly higher in the RG at all time points, the mean VAS pain score in the RG was 46.44 ± 8.5, and in the EG 28.33 ± 11.8 (p <0.0001). On the other hand, the VAS satisfaction scores were all the time almost the same in both groups, the mean VAS satisfaction score during the entire monitoring period was 93.41 ± 9.1 in the RG, and 94.01 ± 9.5 in the EG, without a statistically significant difference between the two groups (p = 0.688). The results present a significantly lower SaO2 value in the RG and a significantly bigger respiratory rate per minute in the EG at all time points after the onset of analgesia. The average SaO2 was 96.95 ± 1.4 in the RG and 98.22 ± 0.6 in the EG with a statistically significant difference of p <0.00001, while the average respiration rate was 18.67 ± 0.9 in the RG, and 20.85 ± 1.4 in the EG with a statistical significance for p <0.0001. During the entire follow-up period, the difference in both groups was statistically not significant for systolic pressure, but significant for diastolic pressure and pulse. The results of the study present more frequent sedation, nausea and vomiting in the RG, while in the EG there was a more elevated temperature, itching and irregularities in the CTG record. Regarding the newborn, there was no significant difference between the two groups in the Apgar scores, ph, pCO2, pO2, and bicarbonate, while there was a significantly lower value of the base excess in the RG. Conclusion: PCA with remifentanil is less effective for pain relief in patients during labor compared to epidural analgesia, but the satisfaction of patients is equal in both groups. Analgesia with remifentanil is safe for the mother, fetus and the newborn, with minimal side effects. It is impossible to determine a single, effective and safe dose that would be appropriate for all parturients.
Докторска дисертација одбранета во 2017 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Мирјана Шошолчева.